Peran Orientasi Kewirausahaan dalam Memediasi Pengaruh Pembelajaran Kewirausahaan dan Minat Usaha Terhadap Kinerja Usaha - Hidayat, Muhammad (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2024)
This study aims to analyze the influence of entrepreneurial learning and business interest on business performance with entrepreneurship orientation as an intervening variable. The study was conducted on 150 small and medium enterprises (SMEs) in City X who had participated in entrepreneurship training. The research method uses a quantitative approach with the analysis technique of Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the study show that entrepreneurship learning and business interests have a significant effect on entrepreneurial orientation. In addition, entrepreneurial orientation has been proven to have a positive influence on business performance, as well as acting as a mediator in the relationship between business interests and business performance. However, it was found that the indirect influence of entrepreneurship learning on business performance through entrepreneurial orientation was negative. These findings indicate that increased entrepreneurial orientation does not necessarily strengthen the relationship between learning and business performance. Therefore, entrepreneurship training should not only emphasize the technical aspect, but also focus on the formation of adaptive and innovative entrepreneurial attitudes and behaviors